2014
DOI: 10.1016/j.psyneuen.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Stability and predictors of change in salivary cortisol measures over six years: MESA

Abstract: Summary A major challenge in characterizing features of the daily cortisol curve is variability in features over time. Few studies have examined the stability of daily features of the cortisol curve over long periods or the predictors of long term changes. Repeated salivary cortisol measures on 580 adults from the MESA Stress study were used to examine the stability of various features of the daily cortisol curve (wakeup value, the cortisol awakening response (CAR), the early and late decline slope and the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 40 publications
8
50
1
4
Order By: Relevance
“…The use of 2 consecutive days is therefore an advantage over single-day studies. In MESA, long-term stability over 6 years is moderate (intraclass correlation 0.25 for the early decline and 0.42 for the late decline) (38). Variability in both sleep and cortisol over time may have attenuated the estimates of the true associations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 2 consecutive days is therefore an advantage over single-day studies. In MESA, long-term stability over 6 years is moderate (intraclass correlation 0.25 for the early decline and 0.42 for the late decline) (38). Variability in both sleep and cortisol over time may have attenuated the estimates of the true associations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have found low short-term stability in CAR and the diurnal slope and these HPA parameters are sensitive to situational factors that can result in their day-to-day fluctuations (Ross et al, 2014; Stalder et al, 2016; Wang et al, 2014). Evidence suggests better short-term stability for total daily cortisol output (Rotenberg et al, 2012; Wang et al, 2014). Suggestions on the number of sampling days have varied and depend on the specific HPA parameter.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate the data in the literature showing that despite use of different psychological instruments, practicing yoga had mental beneficial effects. 10 These feelings may related to an increase in the cortisol levels in the morning and a decrease in the cortisol levels before sleep.…”
Section: Discussionmentioning
confidence: 99%